(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
In this article, in recent years in our republic, for the purpose of taxation in the country, the theoretical and legal basis of the real estate tax, as well as the determination of the cadastral values and the elimination of violations by tax authorities using the instruments of tax administration, the tax system scientific-practical conclusion and suggestions on implementation of measures for timely disclosure of tax evasion schemes, further optimization of tax administration, elimination of contradictions in legal documents have been developed.